Abya Yala's Disability: Weaving With the Thread and Breath of the Ancestors - Alexander Yarza de los Ríos (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: Abya Yala; ancient cosmovision; Indigeneity; jágagɨaɨ; ancient story